Studi Kesesuaian Lahan untuk Pengembangan Silvofishery Kepiting Bakau di Area Mangrove Banyuurip, Ujungpangkah, Gresik - Nur Maulida Safitri; Aminin Aminin; Ummul Firmani (BEST Journal (Biology Education, Sains and Technology), 2022)
The mangrove ecosystem is home to various coastal biota, including the mangrove crab (Scylla spp.). This crab is found practically in all coastal water overgrown with mangroves and can adapt well to high salinity. Banyuurip’s mangrove features environmental characteristics as well as a relatively large diversity of mangrove species, making it suitable for silvofishery farming. In this study, line transects and remote sensing analyses utilizing Landsat 8 satellite imagery were employed at 5 research sites using the ArcGIS v.9.0 and ENVI v.11.0 map processing appliations. The ImageJ program was used to determine the percentage of mangrove coverage data. The results revealed a dominance of Avicennia marina, Bruguiera cylindrica, Rhizopora stylosa, Rhizopora mucronata, Ceriops tagal, and Sonneratia alba mangroves scattered at least at two stations along the waters of Banyuurip Beach, where mangrove crabs preferred the leaf litter of these mangrove species. The percentage of coverage in the mangrove region at stations 1-5 is medium to tight, ranging from 23.56±8.75 – 68.14±7.77%. Stations 1-3 were found to be good for cultivating adult crabs, whereas stations 4-5 were found to be excellent for immature crabs. The amount of mangroves is expected to rise from 1249.578 Ha to 1546.215 Ha between 2018 and 2022. The overlay findings demostrate that there is potential mud crab cultivation using the silvofishery method, with the total area available for early stage development is 342.603 Ha.